LIBRARY AS AN ASPECT OF SUPPORTING OF LITERATURE LEARNING: (The Indonesian Education Character in the Era of the Industrial Revolution 4.0 At The Socio Educational Perspective) - BAKHTIYAR (CV KULTURA DIGITAL MEDIA, 2020)
The research aims to describe the role of the school library as a major supporter of literary learning in character formation. The object of research is focused on the role of libraries in supporting literary learning. The scope of research focuses the role of libraries in supporting character education. The essence of the library as a component of the education system supports learning with information services. Analyzing required critical thinking realistically apply the conceptual using the historical approach. Primary information sources are considered primary data. Collecting data utilizing library research, reading various literature subjected to the role of libraries, learning literature to form characters. Qualitative descriptive analysis by analyzing various collections of theoretical, research and non-research libraries. Valid analysis uses content analysis, to analyze the meaning of the role of library concepts, literary learning, character building, through the empowerment of library services and the application of literary learning activities. Observation is used to support the construction of theory. All successes in literary education in the formation of character in industrial times 4.0, the essence always depends on the role of the library.